2020
DOI: 10.1177/0361198120906423
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Rubber Swelling in Bitumen

Abstract: Rubber swelling in bitumen, which is a diffusion-induced volume expansion process, plays a dominant role in the design of crumb rubber modified bitumen binders and their properties development. This study aims to investigate the kinetics of bitumen diffusion into truck tire rubber, the equilibrium swelling characteristics of rubber, and the mechanical properties of rubber before and after swelling at different high temperatures. Fourier transform infrared spectroscopy results indicate that no rubber dissolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…e number of loading cycles to failure has been defined as fatigue life, more especially in the strain-controlled mode. Several researchers used the peak in the phase angle approach to evaluate the fatigue life of asphalt binders, mastics, and mixtures [52,53]. According to this approach, a point showing the maximum phase angle is a reasonable fatigue failure point, since the phase angle versus time curve shows a rapid loss of the phase angle when asphalt no longer accumulates distress.…”
Section: Time Sweep (Ts) Test Failure Definitionmentioning
confidence: 99%
“…e number of loading cycles to failure has been defined as fatigue life, more especially in the strain-controlled mode. Several researchers used the peak in the phase angle approach to evaluate the fatigue life of asphalt binders, mastics, and mixtures [52,53]. According to this approach, a point showing the maximum phase angle is a reasonable fatigue failure point, since the phase angle versus time curve shows a rapid loss of the phase angle when asphalt no longer accumulates distress.…”
Section: Time Sweep (Ts) Test Failure Definitionmentioning
confidence: 99%
“…For CRM modified binders, Figure 13c shows a swollen rubber particle embedded in the bitumen matrix with a multilayer structure due to the process of sequential diffusion of bitumen into the rubber [36]. In addition, previous studies have shown that swollen rubber is softer than bitumen at the intermediate temperature of 20 C [37]. When the fatigue cracks initiated in the rigid bitumen phase start to propagate, they will meet the swollen rubber particle.…”
Section: Fatigue Cracking In Binders Under Dynamic Shear Loadingmentioning
confidence: 93%
“…The CR chains physically interact with the asphalt binder by adsorbing the light components of the binder (saturates and nonpolar aromatics). As a result, the CR chains swell to be 3–5 times their original size and form the gel phase. , Therefore, the binder colloid of CRMB is a two-phase structure, a gel phase surrounded by a liquid phase. The liquid-phase binder is dominated by the heavy components (asphaltene and resin), which are left after the adsorption of light components by the CR chains .…”
Section: Materials and Binder Preparationmentioning
confidence: 99%